Perrotta Integrative Clinical Interviews (PICI-2): Innovations to the first model, the study on the new modality of personological investigation, trait diagnosis and state diagnosis, and the analysis of functional and dysfunctional personality traits. An - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2021)
Purpose: As a result of clinical findings it is necessary to make some changes to the previous model, the first version. The second version of the PICI model (Perrotta Integrative Clinical Interviews) improves the previous version by introducing some interpretative corrections, especially with regard to dysfunctional hyperactivation, unitary diagnosis, symptomatological persistence, categorical absorption, trait diagnosis and state diagnosis, egosyntony and egodystonia, reducing the items from 150 to 128 for the PICI-2C questionnaire and from 195 to 173 for the PICI-2TA questionnaire. The second version of the PICI is also enriched by a third questionnaire, PICI-2FT, always administered by the therapist after the clinical interview, with 18 items, capable of investigating functional personality traits and thus completing in a more descriptive way the personality picture of the patient in its functional and structural totality.  Methods: Clinical interview, administration of the PICI-2TA and MMPI-II.  Results: With a population sample of 718 participants (310 males and 408 females), performing first a clinical interview, then the PICI-2TA and finally the MMPI-II, a comparison of 99.7% of the results was valid, while the remaining 0.3% seems to be attributable to circumstances that can be identified, such as the interpretative limits of the theoretical model of the MMPI-II, a psychodiagnostic error during the previous diagnosis and the psychopathological evolution of the previously identified disorder. For reasons of theoretical differences in the models, it is not possible to carry out the same analysis for the PICI-1 children's version (C), as the reference nosography also changes with respect to the DSM-V.  Conclusions: This research demonstrated the efficacy, efficiency and psychodiagnostic reliability of the "Perrotta Integrative Clinical Interviews" (PICI-2), version for adolescents and adults (TA), in relation to the evidence obtained by comparing the data with the Minnesota Multiphasic Personality Inventory (MMPI-II). In particular, in the PICI-2 some aspects not identified by the MMPI-II emerged, extremely useful to better profile the patient and proceed in a more systematic way to the specific clinical treatment. It is important to remember that the administration of the PICI-2 photographs the historical moment of the patient and not the previous one; therefore, it may happen that some results are conditioned or distorted by the positive or negative historical moment that the patient is living; it is the duty of the therapist to frame in a clear and exhaustive way the anamnestic universe of the patient in order to understand possible overactivations or omissions of activation following a moment of stability of the patient, which in reality hide the real extent of his clinical manifestation. psychopathological tendency, net of external reinforcements such as the family and the social context.